Novel stability indicating methods for the determination of certain synthetic estrogen level modifiers - Hanan A. Merey; Maha M. Galal; Maissa Y. Salem; Ezzat M. Abdel-Moety (Faculty of Pharmacy, Cairo University, 2013)
Tamoxifen citrate (TC) and raloxifene hydrochloride (RH) are two selective estrogen receptor modifiers. TC is usually used in the treatment of breast cancer while RH is used in the treatment of osteoporosis. Two stability indicating methods, namely, first derivative of ratio spectra (1DD) and TLC-densitometric method are used for the determination of TC in the presence of its photodegradants and RH in the presence of its oxidative degradants. For the first derivative of ratio spectra method, TC was quantitatively measured at 263 nm and 298.2 nm in a concentration range of 10-60 μg/mL while RH was determined at 267.6 nm in a concentration range of 2-18 μg/mL. In the spectro-densitometric method, TC was separated from its photodegradants using a developing system consisting of acetonitrile: 33% ammonia solution (10: 0.1, v/v) in a concentration range of 6-20 μg/band while RH was separated from its oxidative degradants using ethyl acetate: methanol: 33% ammonia solution (7: 3: 0.1, by volume) as a developing system in a concentration range of 3-11 μg/band. The two methods were successfully applied for the stability indicating the determination of the two drugs in a pure powdered form and a pharmaceutical dosage form and showing good recoveries. Statistical comparison between the results obtained by applying the proposed methods and the official method or the reported method for TC and RH, respectively was done and no significant difference was found at p = 0.05.